Variation of polypharmacy in older primary care attenders occurs at prescriber level - Ong, Su Miin; Lim, Yvonne Mei Fong; Sivasampu, Sheamini; Khoo, Ee Ming (BMC, 2018)
Background: Polypharmacy is particularly important in older persons as they are more likely to experience adverse events compared to the rest of the population. Despite the relevance, there is a lack of studies on the possible association of patient, prescriber and practice characteristics with polypharmacy. Thus, the aim of this study was to determine the rate of polypharmacy among older persons attending public and private primary care clinics, and its association with patient, prescriber and practice characteristics. Methods: We used data from The National Medical Care Survey (NMCS), a national cross-sectional survey of patients' visits to primary care clinics in Malaysia. A weighted total of 22,832 encounters of patients aged ≥65 years were analysed. Polypharmacy was defined as concomitant use of five medications and above. Multilevel logistic regression was performed to examine the association of polypharmacy with patient, prescriber and practice characteristics. Results: A total of 20.3% of the older primary care attenders experienced polypharmacy (26.7%% in public and 11.0% in private practice). The adjusted odds ratio (OR) of polypharmacy were 6.37 times greater in public practices. Polypharmacy was associated with patients of female gender (OR 1.49), primary education level (OR 1.61) and multimorbidity (OR 14.21). The variation in rate of polypharmacy was mainly found at prescriber level. Conclusion: Polypharmacy is common among older persons visiting primary care practices. Given the possible adverse outcomes, interventions to reduce the burden of polypharmacy are best to be directed at individual prescribers.